2018
DOI: 10.1007/s00586-018-5489-0
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS PRIZE IN BIOENGINEERING SCIENCE 2018: dynamic imaging of degenerative spondylolisthesis reveals mid-range dynamic lumbar instability not evident on static clinical radiographs

Abstract: Level V data These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 33 publications
(36 reference statements)
3
47
0
1
Order By: Relevance
“…Our system's overall RMSE at the cervical spine ranged between 0.21-0.49 mm and 0.42-1.80˚and at the lumbar spine ranged between 0.35-1.17 mm and 0.49-1.06˚for flexion and lateral bending motions. Results for both of these validations are reasonable given the results of previous works [14,16,20,21], although differences in methods, analysis, and subjects make direct comparison challenging and limited. Anderst et al examined cervical spine 2D/3D shape-matching against RSA in human subjects undergoing cervical spine fusion and found an average segmental tracking precision of 0.19 mm for non-fused bones and an average intersegmental tracking precision of 0.4 mm and 1.1˚for all bones including fused bones for flexion/extension and axial rotation [16].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our system's overall RMSE at the cervical spine ranged between 0.21-0.49 mm and 0.42-1.80˚and at the lumbar spine ranged between 0.35-1.17 mm and 0.49-1.06˚for flexion and lateral bending motions. Results for both of these validations are reasonable given the results of previous works [14,16,20,21], although differences in methods, analysis, and subjects make direct comparison challenging and limited. Anderst et al examined cervical spine 2D/3D shape-matching against RSA in human subjects undergoing cervical spine fusion and found an average segmental tracking precision of 0.19 mm for non-fused bones and an average intersegmental tracking precision of 0.4 mm and 1.1˚for all bones including fused bones for flexion/extension and axial rotation [16].…”
Section: Discussionsupporting
confidence: 79%
“…The present study found comparable values to Anderst et al; however, both precision and RMSE values were higher than McDonald et al Potential differences in bead placement, testing setup, and differences between human and ovine anatomy make the results difficult to compare directly, but may explain some of the difference between studies. Previous lumbar spine 2D/3D shape-matching versus RSA validation works have been done by Wu et al in a cadaveric model and Dombrowski et al in vivo [20,21]. Wu et al examined an MRI bone model 2D/3D shape-matching at five positions throughout flexion and extension and found the average biplane shape-matching bias of a single segment/bone to be within 0.30 mm and 0.74˚and precision to be within 0.39 mm and 0.83˚across all planes of motion when compared to RSA [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When L4‐L5 rotation varied by ±3° (the largest inter‐rater error), IDP changed by less than 10%, from its reference value of 1.86 MPa to 2.06 MPa (for an error of 3° in flexion) and to 1.78 MPa (for an error of 3° in extension). Recent studies, however, have reported considerably smaller errors of ~0.4° to 0.9° and 0.2° to 0.3 mm in MR‐ or CT‐based measurements of vertebral rotations and translations, respectively . Our FE model, when driven by kinematics from more accurate recent imaging techniques, is therefore expected to generate more reliable predictions.…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies, however, have reported considerably smaller errors of~0.4°to 0.9°and 0.2°to 0.3 mm in MR-or CT-based measurements of vertebral rotations and translations, respectively. 10,11,[34][35][36] Our FE model, when driven by kinematics from more accurate recent imaging techniques, is therefore expected to generate more reliable predictions.…”
Section: Limitationsmentioning
confidence: 99%